PENGEMBANGAN APLIKASI WEB PARIWISATA DANAU TOBA BERBASIS KOMUNITAS (VISIT TOBA) - Yohanssen Pratama; Riyanthi A Sianturi; Helmuth S Tampubolon; Kristopel Lumbantoruan; Hotni M Simatupang; Indah T Tampubolon; Yohana C Manullang (J-ICON : Jurnal Komputer dan Informatika, 2022)
The problem faced by several tourist destinations in the Lake Toba Region is that branding has not been maximized using digital media. In this study, we have the goal of developing the VisitToba Community Based Tourism (CBT) application to develop the tourism potential of the Lake Toba area through digitalization with the concept of community empowerment, improving the quality of tourism and the economy of the tourism community in the Lake Toba area. The Visit Toba application is expected to be a forum for the development of local small and medium-sized businesses as tourism supporters, where tourism actors can take advantage of the features in this application to be able to collaborate with each other to make a tour package. Increased community participation in efforts to develop and strengthen tourism in the Lake Toba area is the expected result with this application, so that a partnership is established between tourism entrepreneurs in the Lake Toba area with the tour packages provided. Applications built using the Waterfall model and have passed the testing phase so that the results in the form of a website can already be implemented in the Lake Toba area.